Attention-deficit hyperactivity disorder (ADHD) stimulant medications as cognitive enhancers - Advokat, Claire D.; Scheithauer, Mindy (Frontiers in Neuroscience, 2013)
Recent increases in ADHD diagnoses, and the escalation of stimulant prescriptions, have raised concern about diversion and abuse of stimulants, as well as the ethics of using these drugs as ‘cognitive enhancers.’ Such concern appears misplaced in the face of substantial evidence that stimulant drugs do not improve the academic performance of ADHD-diagnosed students. Moreover, numerous studies have found little or no benefit of stimulants on neuropsychological tests of ADHD-diagnosed as well as normal, individuals. This paper examines the apparent paradox: why don’t drugs that improve ‘attention,’ produce better academic outcomes in ADHD-diagnosed students? We found that stimulant drugs significantly improved impairment of episodic memory in ADHD-diagnosed undergraduate students. Nevertheless, we also found consistent academic deficits between ADHD students and their nonADHD counterparts, regardless of whether or not they used stimulant medications. We reviewed the current literature on the behavioral effects of stimulants, to try to find an explanation for these conflicting phenomena. Across a variety of behavioral tasks, stimulants have been shown to reduce emotional reactions to frustration, improve the ability to detect errors, and increase effortful behavior. However, all of these effects would presumably enhance academic performance. On the other hand, the drugs were also found to promote ‘risky behavior’ and to increase susceptibility to environmental distraction. Such negative effects, including the use of drugs to promote wakefulness for last minute study, might explain the lack of academic benefit in the ‘real world,’ despite their cognitive potential. Like many drugs, stimulants influence behavior in multiple ways, depending on the environmental contingencies. Depending on the circumstances, stimulants may, or may not, enhance cognition.